Construction of an achievement test for freshmen English for Thai students - Tubplang, Sinee 1932- (Quezon City, Philippines College of Education, University of the Philippines Diliman, 1965)
This study presents a constructed achievement test in Freshmen English for Thai students in Pisanuloke Teachers' College based on the instructional objectives of a course of study, and textbooks in use at present in that institution. The procedures used in developing the test are as follows: test planning, preparation of the test, try-out of the preliminary test and refining of the test by item analysis method.
Thesis (Master of Education)--University of the Philippines Diliman
Keywords: Universities and colleges -- Examinations